Luminous Color in Architecture: Exploring Methodologies for Design-Relevant Research - Besenecker, Ute Christa; Krueger, Ted (Enquiry The ARCC Journal for Architectural Research, 2015)
This paper describes our process in conducting research toward better understanding of the experience and perception of luminous colors in architectural contexts. Our intention is to contribute to a body of knowledge useful for designers by introducing a designerly way of working into an otherwise academic research approach. Luminous color influences our perception of form, space, and ambiance. The use of such color in architectural design has increased significantly over the past two decades, and with the advent of light-emitting diodes (LEDs), this trend is rapidly accelerating. However, LEDs produce luminous color in a different manner than traditional lighting systems. Identical-appearing colors can have different spectral compositions. Current work in health and perception sciences demonstrates that these different spectra can have distinct physiological and neurological effects. Current studies in different academic research fields into luminous color cannot be translated easily into a format relevant to architectural design. We therefore look to ways of studying the phenomenon using hybrid methods that would be consistent with design disciplines and goals. Efforts include structured experimental studies at a large scale to enable participants to experience different vantage points, peripheral perceptions, and free locomotion. The objective is to listen to the phenomenon and let it guide the research. We are following a process and developing research methods that are at a scale and in contexts appropriate to architectural applications. Although we borrow qualitative and quantitative methods from other disciplines for our individual studies, the overall goal is to remain fluid and open, to go beyond such established methods, structuring the endeavor as much as possible as a design process. Our approach is less structured than laboratory research, but targeted to be more ecologically and architecturally valid.